Labour productivity in state-owned enterprises - António Afonso; Maria Jo\~ao Guedes; Pankaj Patel (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
In the aftermath of the Global and Financial Crisis (GFC), between 2013 and 2015, the Portuguese government revoked four holidays for both public sector and private employees. We test whether the revocation had an effect on labour productivity in State-Owned Enterprises (SOEs) in Portugal. Moreover, we also study whether such effects are different taking into account the SOEs managed by the Central Government or the Local and Regional Governments. Our results show that revocation of holidays did not impact labour productivity for either central or local and regional government managed SOEs. Though revocation of holidays espoused to improve productivity, the policy seems to have served a ceremonial purpose, but not an economic one.
Keywords: C23; H79; J45; J58; J89; L32; 330; labour productivity; state-owned enterprises; central government; panel data; Portugal